Inovasi Desain Microteaching: Meningkatkan Kemampuan Pedagogik Mahasiswa - Azizah, Nurul; Umami, Halida; Mufidah, Zuhrotul; Mulyadi, Ilham; Aslamiyah, Siti Suwaibatul (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to describe the innovation in the microteaching program design implemented by the Faculty of Tarbiyah at UNIDA Gontor through the Teacher Training Development Program (TTDP). Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis. The findings reveal that the program’s success is supported by the systematic integration of theory and practice. Innovations include theoretical guidance on basic teaching concepts, workshops and mentoring by expert lecturers in lesson plan development, selection of model teachers, teaching practice using relevant curriculum materials in pesantren, schools, and madrasahs, and an emphasis on active learning models.